Pengaruh Biaya Lingkungan, Kinerja Lingkungan, Modal Intelektual Hijau dan Kepemilikan Institusional terhadap Pengungkapan Emisi Karbon: Studi Empiris pada Perusahaan Pertambangan dan Material Dasar yang Terdaftar di BEI Periode 2022 – 2024 - Pratama, Rahmadyan Putra; Negara, Hari Kusuma Satria (Jurnal Eksplorasi Akuntansi, 2026)
This study aims to obtain empirical evidence on the effect of environmental costs, environmental performance, green intellectual capital, and institutional ownership on carbon emission disclosure. The population of this study consists of mining and basic material companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This study employs secondary data and uses purposive sampling, resulting in a total sample of 47 companies with 141 firm-year observations. Panel data analysis is applied to examine the proposed relationships. The results indicate that environmental costs, environmental performance, and green intellectual capital have a positive and significant effect on carbon emission disclosure. Meanwhile, institutional ownership has a significant negative effect on carbon emission disclosure. This study contributes to the carbon emission disclosure literature by providing empirical evidence from mining and basic material companies in Indonesia, while also enriching the application of legitimacy and stakeholder theories in explaining corporate environmental disclosure practices.